Serum Levels of Soluble CD40 Ligand and Neopterin in HIV Coinfected Asymptomatic and Symptomatic Visceral Leishmaniasis Patients - Adriaensen, Wim; Abdellati, Saïd; van Henten, Saskia; Gedamu, Yonas; Diro, Ermias; Vogt, Florian; Mengesha, Bewketu; Adem, Emebet; Kestens, Luc; van Griensven, Johan (Frontiers in Cellular and Infection Microbiology, 2018)
Human Immunodeficiency Virus (HIV) co-infection drastically increases the risk of developing overt visceral leishmaniasis (VL). The asymptomatic Leishmania infection window constitutes an opportunity to identify those HIV patients at highest risk by defining early markers associated with disease susceptibility or resistance. As intracellular parasite killing is essential, we investigated whether serum markers of macrophage activation were notably affected in HIV patients with an asymptomatic Leishmania infection or overt visceral leishmaniasis disease. Serum levels of soluble CD40 ligand and neopterin were assessed in 24 active VL-HIV patients, 35 HIV patients with asymptomatic Leishmania infection and 35 HIV endemic controls. All patients were recruited in L. donovani endemic regions of North-West Ethiopia. The serum levels of sCD40L and neopterin significantly decreased and increased in HIV patients with active VL compared to HIV patients with asymptomatic Leishmania infection, respectively. No statistically significant differences could be detected in neopterin and sCD40L levels between Leishmania asymptomatically infected HIV patients and endemic HIV control patients. However, an inverse trend, between Leishmania antibody positivity or VL development and neopterin levels could be seen. The CD4+ T-cell count was inversely correlated with serum neopterin levels, but not with sCD40L levels. Our results in HIV coinfected patients, correspond with the postulated protective role of sCD40L in VL and underline the importance of the CD40-CD40L pathway in resistance against the parasite. Neopterin levels suggest an increased macrophage activation upon infection and could have a value in clinical algorithms to, although non-specifically, improve prediction of VL development in HIV patients with asymptomatic Leishmania infection.